Towns, tenements and buildings: aspects of medieval urban archaeology and geography - Baker, Nigel (1990)
This thesis will argue that the most effective way of understanding the physical development of medieval towns, particularly the larger, more complex, towns and those which lack extensive and detailed contemporary documentation is by a structured integration of the data derived from the archaeological investigation of individual sites with detailed town-plan analyses following the methodology introduced and developed by Conzen. This will be demonstrated by two case-studies, designed to explore the Interaction of the different sources of evidence at two different scales of investigation.